Diffusion-weighted MRI to determine response and long-term clinical outcomes in muscle-invasive bladder cancer following neoadjuvant chemotherapy - Hafeez, Shaista; Koh, Mu; Jones, Kelly; Ghzal, Amir El; D’Arcy, James; Kumar, Pardeep; Khoo, Vincent; Lalondrelle, Susan; McDonald, Fiona; Thompson, Alan; Scurr, Erica; Sohaib, Aslam; et al. (Frontiers in Oncology, 2022)
Abstract Objective To determine local treatment response and long-term survival outcomes in patients with localised muscle invasive bladder cancer (MIBC) patients receiving neoadjuvant chemotherapy (NAC) using diffusion weighted MRI (DWI) and apparent diffusion coefficient (ADC) analysis. Methods Patients with T2-T4aN0-3M0 bladder cancer suitable for NAC were recruited prospectively. DWI was performed prior to NAC and was repeated following NAC completion. Conventional response assessment was performed with cystoscopy and tumour site biopsy. Response was dichotomised into response (T2). Patients proceeded to either radical cystectomy or chemo-radiotherapy as standard of care. Tumour ADC values was calculated for all b values (ADCall) and high b values (ADCb100). Mean ADC, percentiles, skew, kurtosis, and their change (ΔADC and %ΔADC) was determined. Threshold predictive of response with highest specificity was ascertained using ROC analysis. Median overall survival (OS), bladder cancer specific survival (bCSS), progression free survival (PFS), and time to cystectomy were estimated using Kaplan Meier method. Significant AUC cut points were used to determine relationship with long-term endpoints and were compared using log-rank test. Results Forty-eight patients (96 DWI) were evaluated. NAC response was associated with significant increase in mean ADC and %ADC compared to poor response (ADCall 0.32x10-3mm2/s versus 0.11x10-3mm2/s; p=0.009, and %ADCall 21.70% versus 8.23%; p=0.013). Highest specificity predicting response was seen at 75th percentile ADC (AUC 0.8; p=0.01). Sensitivity, specificity, positive predictive power, and negative predictive power of %ADCb100 75th percentile was 73.7%, 90.0%, 96.6%, and 52.9% respectively. %ΔADCb100 75th percentile >15.5% was associated with significant improvement in OS (HR 0.40, 95% CI 0.19-0.86; p=0.0179), bCSS (HR 0.26, 95% CI 0.08-0.82; p=0.0214), PFS (HR 0.16, 95% CI 0.05-0.48; p=0.0012), and time to cystectomy (HR 0.19, 95% CI 0.07-0.47; p=0.0004). Conclusions Quantitative ADC analysis can successfully identify NAC response and improved long-term clinical outcomes. Multi-centre validation to assess reproducibility and repeatability is required before testing within clinical trials to inform MIBC treatment decision making.